A search for the most accurate formula for sonographic weight estimation by fetal sex – a retrospective cohort study1. (17th September 2014) - Barel, O.; Maymon, R.; Barak, U.; Smorgick, N.; Tovbin, J.; Vaknin, Z.
<x xml:space="preserve">Abstract</x> What's already known about this topic? There is conflicting evidence regarding the influence of fetal sex on the accuracy of fetal weight estimation. Sex‐specific formulas were developed in an effort to improve the accuracy of sonographic weight estimation. Although several sex‐specific models were evaluated in the literature to date, the comparisons included a relatively small number of patients. So far, no one single model has proven to be a preferred method for estimating fetal weight. What does this study add? This study evaluated over 6500 cases and found a significant effect of fetal sex on the accuracy of sonographic fetal weight estimation. In our research population, we saw that using a combination of two formulas to estimate fetal weight provided significantly more accurate fetal weight estimation.